Contribution of regulatory T cells to immunosuppression and disease progression in multiple myeloma patients - Raja, Karthick Raja Muthu; Hajek, Roman (Oncoimmunology, 2013)
Multiple myeloma (MM) patients exhibit consistent degrees of immune dysfunction. Regulatory T cells contribute to the establishment of an immunosuppressive status in MM patients, hence favoring disease progression.
Keywords: immune suppression; T regulatory cells; FoxP3; suppressor cells; multiple myeloma; disease progression